The The effectiveness of dialectical behavior therapy (DBT) in reducing suicide risk among psychiatric patients: A systematic review - Irma Sofiani Kusmara; Mustikasari Mustikasari; Novy Helena Catharina Daulima; Yossie Susanti Eka Putri (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Suicide is a major public health concern and one of the leading causes of death globally, particularly among individuals with psychiatric disorders. Various psychotherapeutic interventions have been developed to reduce suicide risk, including Dialectical Behavior Therapy (DBT), which has shown promising results in patients with borderline personality disorder (BPD) and other psychiatric diagnoses Purpose: To systematically review the effectiveness of DBT in reducing suicidal ideation, suicide attempts, and self-harm behaviors in adult psychiatric patients. Method: A systematic search was conducted through PubMed, Scopus, and ClinicalKey Nursing for articles published between 2010 and 2025. Inclusion criteria encompassed randomized controlled trials and quasi-experimental studies involving DBT as the main intervention. Results: A total of eight studies (seven RCTs and one quasi-experimental) met the criteria. The results indicate that DBT significantly reduces suicidal ideation, suicide attempts, and non-suicidal self-injury (NSSI), particularly when the skills training component is included. DBT was found to be equally or more effective than treatment as usual (TAU), cognitive behavioral therapy (CBT), and other interventions. Key factors influencing effectiveness included therapist fidelity, patient engagement, and contextual implementation. Conclusion: This review concludes that DBT is a robust, evidence-based approach to suicide prevention in psychiatric settings and recommends its comprehensive implementation in clinical practice.